Noise-induced hearing loss in bus and truck drivers in Mazandaran province, 2011. Issue 2 (2nd April 2016) - Alizadeh, Ahmad; Etemadinezhad, Siavash; Charati, Jamshid Yazdani; Mohamadiyan, Mahmood
Abstract : Background and purpose. Noise-induced hearing loss (NIHL) is among the most prevalent and preventable work-related disorders. This study was conducted to evaluate the prevalence and severity of NIHL in bus and truck drivers of Mazandaran province in north Iran. Materials and methods. In a cross-sectional descriptive study, 2283 drivers were examined clinically and para-clinically, including measuring their fasting blood sugar, triglyceride and cholesterol levels. All participants were evaluated for the air and bone thresholds of both ears. Twenty-three individuals were excluded from the study because of conductive hearing loss. Data from 2260 drivers were analyzed using SPSS version 18. Results. Of the drivers, 37.5% had hearing loss in the right ear and 41.8% of the drivers had hearing loss in the left ear in one or more frequencies of sound. Hearing loss was significantly more frequent in the left ear and in 6000 Hz followed by 4000 Hz. Conclusion. Our study showed that the prevalence and severity of NIHL is high in drivers of Mazandaran province. There was a correlation between hearing loss and age and driving work history. We recommend considering hearing conservation programs more seriously.